Enjeux intertextuels dans le roman « Loin de Médine » de Assia DJEBAR (مجلة الواحات للبحوث والدراسات, 2015)
The present studyaims to describe and analyze the variouspractices and manifestations of intertextualityin the historical novel "Farfrom Medina" written by Assia DJEBAR. It is meantto show howintertextualityaswriting processoffers the possibility of transpositionof a speech (historical)  in another speech (fictional). Thisgives birth to ahybrid genre: the historical novel. "Farfrom Medina" is accordingly, a privileged spaceexploration of this genericspecificityand significantdiscursiveheterogeneity. This paper will shed light on the historical novel in general and that of ASSIA DJEBBAR in particular.Keywords: Intertextuality, historical novel,discursiveheterogeneity, textualstratification,orality/writing process.